Contributions regarding increasing efficiency of attack by applying regimes contractions alternated in volleyball - Cojocaru, A. M.; Cojocaru, M. (Science, Movement & Health, 2016)
Aim. The major role that it has the strength to practice volleyball performance modeling training requires taking into account the impact it has this motor skill in obtaining significant results in competitions. The players build and maintain a high level of performance, develop muscle groups in a homogeneous form without imbalances that disrupt subsequent training and sports performance. The aim of research is to make better use in preparing attack hit muscle contractions alternating regimens tailored to the tasks of the game. Methods. As a working method I used: - bibliographic documentation; - interpretation of statistical and mathematical method; - graphical representation method; Results. From the graphical representation of the results, the efficiency of the whole team attack strikes, initial testing efficiency value was 26% and 31% final testing, so there is a 5% improvement. This result enables us to believe that muscle training programs by alternating regimens had a decisive role in increasing the efficiency of attack.. Conclusions. For this purpose we recommend the use of force in preparing classical methods, depending on the forms of labor they require volleyball and methods based regimens contraction in preparation alternate Is recommend this method to not cause monotony in preparation and foster conscious and active participation of athletes in training lessons.